Arabic Science Fiction - Campbell, Ian (Studies in Global Science Fiction,, 2018)
This book traces the roots of Arabic science fiction through classical and medieval Arabic literature, undertaking close readings of formative texts of Arabic science fiction via a critical framework developed from the work of Western critics of Western science fiction, Arab critics of Arabic science fiction and postcolonial theorists of literature. Ian Campbell investigates the ways in which Arabic science fiction engages with a theoretical concept he terms "double estrangement" wherein these texts provide social or political criticism through estrangement and simultaneously critique their own societies' inability or refusal to engage in the sort of modernization that would lead the Arab world back to leadership in science and technology.